Differentiated Learning Strategies in Improving Science Learning Achievement in Elementary Schools - Muhib, Muhammad (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the effectiveness of differentiated learning strategies in improving learning achievement in Natural Science (IPA) in elementary schools. Differentiated learning is important because each student has different needs, abilities, and learning styles. By implementing this strategy, it is expected to provide a more personal and effective learning experience, which in turn can improve students' understanding of science materials and their learning achievement. This study uses the Systematic Literature Review (SLR) approach to evaluate various previous studies that examine the application of differentiated learning in the context of elementary education. The results of the analysis show that differentiated learning has a positive impact on student learning achievement in science. The use of this approach allows teachers to adjust teaching methods and materials according to the abilities and needs of each student, which ultimately increases student motivation, engagement, and learning outcomes. This study also identified several factors that influence the success of implementing differentiated learning in elementary schools, such as teacher competence, learning facilities, and student readiness. Therefore, it is recommended that elementary schools implement this strategy adequately in order to improve the quality of science learning.